Geochronological and geochemical constraints on the origin of the Southeast Anatolian ophiolites, Turkey - Bingol, A. Feyzi; Beyarslan, Melahat; Lin, Yu-Chin; Lee, Hao-Yang (Springer Heidelberg, 2018)
The Southeast Anatolian ophiolites outcropping in the Southeast Anatolian Orogenic Belt (Southeast of Turkey) mark the closure of the southern branch of the Neotethys Ocean associated with the collision between the Arabian Plate and Anatolian microplate. We present new geochemical, zircon U-Pb age, zircon Lu-Hf, and Sr-Nd isotopic data on the Southeast Anatolian Ophiolites to understand their formation ages, magma genesis, and geotectonic implications. The ophiolites, which are related to island arc igneous rocks, consist of mantle peridotites and crustal rocks (less dunite, gabbros, sheeted dykes, massive, and pillow basalts). The flat rare-earth element (REE) patterns, depletion in Nb and Ta, and enrichment in LILEs (Ba, Rb, Th, Sr, Pb) of gabbros suggest close similarities with very low Ti (boninitic) lavas found in the forearc regions. Using laser ablation inductively coupled plasma-mass spectrometry, zircon separated from leucogabbros, diabase dykes, and plagiogranites yield U-Pb ages of 92 and 83Ma, which are interpreted to represent the formation ages of the ophiolites. The zircons in the gabbros and plagiogranites are dominated by positive epsilon Hf(t) values (between +3.1 and +17.45) with a few negative epsilon Hf(t) values. High epsilon Hf(t) features are consistent with derivation from Mid-oceanic Ridge Basalt (MORB)-source mantle. The negative epsilon Hf(t) values of the zircons suggest the involvement of subducted sedimentary rocks. The southeast Anatolian ophiolites represent an SSZ-type ophiolite and are part of the Late Cretaceous oceanic lithosphere of the southern branch of the Neotethys Ocean that opened during the Late Triassic and closed during the Late Cretaceous.
Keywords: Ophiolite; Mantle peridotite; Crustal rocks; Zircon age; Hf isotope